Market efficiency and its impact on share price: a study of listed manufacturing companies in sri lanka - Nimalathasan, B.; Nishanthini, A. (University of Jaffna, 2014)
This research on “Market Efficiency and Its Impact on Share price: A Study of Listed Manufacturing Companies in Sri Lanka.” it is designed to give some idea of the relationship between share prices and related variables such as dividend announcement and earning etc. Qualitative approach was utilized in this study, which is conducted by considering the Manufacturing companies. An association in the present study EPS, Share price and dividend announcement could be observed. In this research, AAR and CAR are analyzed based on dividend announcement and correlation and regression are used to identify the relationship between EPS and share price. Based on the quantitative study, EPS has greater impact on Share price. There is positive relationship between EPS and Share price. Dividend announcements aren’t significant in pre period of announcement day. Dividend announcements are significant in post period of announcement day. There is no signaling effect in manufacturing sector companies. The announcement of dividend normally carries no surprise to the market. Evidence tends to conform that market reacts after the dividend announcement. There is positive relationship between dividend announcement and share price. This positive relationship can occur near to the dividend announcement. Informationare conveyed near to the dividend announcement. Sample selection had to be limited because of time & data availability is limited. If information flow is being delayed by CSE, can’t take recent year information to research purpose. Decision of investors in selecting shares may be influenced by accounting information. But this study considers signaling effect of EPS and dividend announcement.
Keywords: Share price; Earnings per share; Dividend announcement